Modeling comparison of lap joint using finite element analysis / W. Kuntjoro ... [et al.] - W., Kuntjoro; M. Latip, Ummu H.; M. Nasir, Rizal E.; R., Ramly (Smart Manufacturing Research Institute (SMRI), 2022)
Lap joints are commonly used as a method of connecting structural parts. This includes parts that are made by 3D printing technology. Structural simulation using the finite element (FE) method can be used for lap joint analysis purposes. There are two approaches to use for the analysis of lap joints: actual bolt connection, and virtual bolt connection. Although an actual bolt connection is ideal to use, however in some cases it is impractical, for example when the number of joints and number of fasteners is huge. It is necessary to understand the behavior of these two different approaches for 3D printed lap joints. The modeling comparison of 3D printed PLA lap joint of these two different connections was studied using FE analysis. FE analysis was carried out using CATIA software to determine the Von Misses Stress value and displacement for each type of connection. Comparison between virtual bolt and actual bolt connections showed that actual bolts have higher Von Misses Stress value, while both connections models are having similar displacements. Different pre-tensions on bolts bring small changes to the Von Misses Stress values.